Exploring the Potential of Project Based Education in a Challenging and Motivating Approach for Students - Noor, Sjamsul Alam; Alqadri, Muh; Ashari, Wahyu (Educia Journal, 2024)
The paper examines the possibility of Project-Based Education as an engaging and difficult learning strategy in teaching. The study sought to establish the impact of PBE on students’ experience, motivation and the learning that occurs in relation to students’ support from the teachers. The participants self-selected for the study included 20 students and 6 teachers from a diverse range of disciplines who had engaged in PBE in some form or another. Participants were given semi structured questionnaires and focus group discussions, and classroom observations in which data were analyzed using thematic analysis. The research proves that the use of PBE improved motivation by addressing realistic context and self-organizing learning. When the students were allowed autonomy in the selection of projects and organisation, they said they felt more involved in the lesson. The most salient finding during this study was that teacher support was an important antecedent for PBE, where teachers served as enablers and coaches, as well as being inspirational sources of encouragement. However, other issues that were observed when students collaborated included the problems that were associated with group dynamics as well as time management issues. This work enriches the further development of research results in the following ways: The key concept of PBE, such as implementation of a structured guideline and supportive teacher encouragement to facilitate pupils’ motivation and interest. The research findings are used to make suggestions to teachers concerning how to facilitate scaffold, time and how the class setting can be conducive for PBE.